Answer:
Think of reflect as looking in a mirror. The question should tell you how your reflecting. It might say "reflect the rectangle over the y axis" (Look at the attachment below to see example).
Step-by-step explanation:
I can help more if I see the question. But usually questions ask you to reflect over the y or x axis.
2.
M must be (0,0) since it coincides with the origin
R must be (a+b, √(a²-b²)).
The x-coordinate is b from A translated to the right by a.
The y-coordinate is the same as A.
(I think the square root is there to confuse you).
3.
R(0,0)
C(a,b) (same x as T, same Y as E)
5.
Not sure how to prove that.
<h2>
Hello!</h2>
The answer is:
![Sin(A)=0.93](https://tex.z-dn.net/?f=Sin%28A%29%3D0.93)
<h2>Why?</h2>
To solve the problem, remember to set your calculator in "degree mode"
So, we are given that the angle A is equal to 68°
So, we have that:
![Sin(A)=Sin(68\°)=0.93](https://tex.z-dn.net/?f=Sin%28A%29%3DSin%2868%5C%C2%B0%29%3D0.93)
Hence, we have that:
![Sin(A)=0.93](https://tex.z-dn.net/?f=Sin%28A%29%3D0.93)
Have a nice day!
Yes -4 is a interference number
Since you know the value of "x", you can plug in the value for "x" in the equation.
[When an exponent is negative, you move it to the other side of the fraction to make the exponent positive.]
For example:
or ![\frac{x^{-2}}{1} =\frac{1}{x^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B-2%7D%7D%7B1%7D%20%3D%5Cfrac%7B1%7D%7Bx%5E2%7D)
or y³
x = -2
f(x) = 9x + 7
f(-2) = 9(-2) + 7 = -18 + 7 = -11
![g(x)=5^x](https://tex.z-dn.net/?f=g%28x%29%3D5%5Ex)
(idk if you should have it as a decimal or a fraction)
x = -1
f(x) = 9x + 7
f(-1) = 9(-1) + 7 = -9 + 7 = -2
![g(x)=5^x](https://tex.z-dn.net/?f=g%28x%29%3D5%5Ex)
![g(-1)=5^{-1}=\frac{1}{5}](https://tex.z-dn.net/?f=g%28-1%29%3D5%5E%7B-1%7D%3D%5Cfrac%7B1%7D%7B5%7D)
x = 0
f(x) = 9x + 7
f(0) = 9(0) + 7 = 7
![g(x)=5^x](https://tex.z-dn.net/?f=g%28x%29%3D5%5Ex)
![g(0)=5^0=1](https://tex.z-dn.net/?f=g%280%29%3D5%5E0%3D1)
x = 1
f(x) = 9x + 7
f(1) = 9(1) + 7 = 9 + 7 = 16
![g(x)=5^x](https://tex.z-dn.net/?f=g%28x%29%3D5%5Ex)
![g(1)=5^1=5](https://tex.z-dn.net/?f=g%281%29%3D5%5E1%3D5)
x = 2
f(x) = 9x + 7
f(2) = 9(2) + 7 = 18 + 7 = 25
![g(x)=5^x](https://tex.z-dn.net/?f=g%28x%29%3D5%5Ex)
![g(2)=5^2=25](https://tex.z-dn.net/?f=g%282%29%3D5%5E2%3D25)
You need to determine the solution of f(x) = g(x)
Since you know f(x) = 9x + 7 and
, you can plug in (9x + 7) for f(x), and (
) into g(x)
f(x) = g(x)
You can plug in each value of x into the equation
Your answer is x = 2 because when you plug in 2 for x in the equation, you get 25 = 25